Design And Implementation Of Accounting Recording System At Toko Indah Kasih Using Microsoft Access - Catherine Catherine; Kennardi Tanujaya (Universitas Internasional Batam, 2023)
This community service aims to design a simple accounting recording system that Toko Indah Kasih can use in keeping accounting records. Toko Indah Kasih is a Micro, Small, and Medium Enterprises (MSMEs) located in one of the strategic areas in Tanjungpinang. Based on the results of interviews with the owner, Toko Indah Kasih has difficulties in financial recording. This shop still uses paper in keeping its financial records compared to using the system. The method that will be applied in this research starts from analysis, followed by system design and ends with system implementation. The expected results of this study are an accounting recording system using Microsoft Access which is capable of recording and producing financial reports within a certain period for Toko Indah Kasih. It is a great expectation that Toko Indah Kasih will use this system for future records and produce better financial reports. As for recommendations for future researchers to be able to add new, more interesting innovations that can help MSMEs and business owners, and can update the accounting system in accordance with the times that will occur in the future and make it easier for other MSMEs in recording and reporting finances.